(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe factors associated with the knowledge and practices of malaria prevention among the La Hu ethnic people in Muong Te district, Lai Chau province, in 2025. Subjects and Methods: A cross-sectional descriptive study was conducted on 400 La Hu ethnic individuals through interviews. The study was carried out in three communes - Pa Ve Su, Ta Ba, and Pa U - in Muong Te district, Lai Chau province, from January 2025 to October 2025. Results: Several factors were found to be associated with malaria prevention knowledge and practices among the La Hu people. Individuals with a lower secondary education or below had a 15.8-fold higher risk of inadequate knowledge and a 21.59-fold higher risk of incorrect practices compared to those with higher education levels. Shifting cultivation (farming) was associated with a 4.5 times higher risk of incorrect practice compared to other occupations, reflecting the challenges posed by specific living and working environments. Furthermore, individuals with inadequate knowledge were 46.6 times more likely to demonstrate incorrect practice compared to those with adequate knowledge. Conclusion: Education level is strongly associated with both knowledge and practice. The specific characteristics of shifting cultivation, along with habits such as not using bed nets and neglecting environmental sanitation, significantly increase the risk of incorrect prevention practices.